Combined Effect of Cold Atmospheric Plasma and Hydrogen Peroxide Treatment on Mature Listeria monocytogenes and Salmonella Typhimurium Biofilms - Govaert, Marlies; Smet, Cindy; Verheyen, Davy; Walsh, James L.; Van Impe, Jan F. M. (Frontiers in Microbiology, 2019)
Cold Atmospheric Plasma (CAP) is a promising novel method for biofilm inactivation as log-reduction values up to 4.0 log10 (CFU/cm²) have been reported. Nevertheless, as the efficacy of CAP itself is not sufficient for complete inactivation of mature biofilms, the hurdle technology could be applied in order to obtain higher combined efficacies. In this study, CAP treatment was combined with a mild hydrogen peroxide (H2O2) treatment for disinfection of 1 and 7 day(s) old Listeria monocytogenes and Salmonella Typhimurium biofilms. Three different treatment sequences were investigated in order to determine the most effective treatment sequence, i.e.,i.e. (i) first CAP, then H2O2, (ii) first H2O2, then CAP, and (iii) a simultaneous treatment of CAP and H2O2. Removal of the biofilm, induction of sub-lethal injury, and H2O2 breakdown due to the presence of catalase within the biofilms were investigated in order to comment on their possible contribution to the combined inactivation efficacy. Results indicated that the preferred treatment sequence was dependent on the biofilm forming species, biofilm age, and applied H2O2 concentration ([0.05 or 0.20 (v/v) %% (v/v)]). At the lowest H2O2 concentration, the highest log-reductions were generally observed if the CAP treatment was preceded by the H2O2 treatment, while at the highest H2O2 concentration, the opposite sequence [(first CAP, then H2O2]) proved to be more effective. Induction of sub-lethal injury contributed to the combined bactericidal effect, while the presence of catalase within the biofilms resulted in an increased resistance. In addition, high log-reductions were partially the result of biofilm removal. The highest overall log-reductions [(i.e.,i.e. up to 5.42±0.33 log10 (CFU/cm²)]) were obtained at the highest H2O2 concentration if CAP treatment was followed by H2O2 treatment. As this resulted in (almost) complete inactivation of the L. monocytogenes and S. Typhimurium biofilms, the combined treatment of CAP and H2O2 proved to be a promising method for disinfection of abiotic surfaces.